Transition metal oxide loaded aluminum oxide hierarchical pore catalytic material as well as preparation method and application thereof

By loading transition metal oxides on a multi-stage porous support of alumina, the composite metal oxide activity center is solved, and the existing heterogeneous catalysts are low in catalytic activity and insufficient stability are achieved, and efficient and stable biodiesel production is achieved.

CN119500103APending Publication Date: 2025-02-25HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661052.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing heterogeneous catalysts have low catalytic activity, insufficient stability and easy carbon accumulation in biodiesel production, resulting in poor stability and catalytic capacity of biodiesel production and low production efficiency.

Method used

A transition metal oxide-supported alumina multi-stage pore catalytic material is developed to improve the catalytic activity and stability of the catalyst by assembling the composite metal oxide activity center on the support, and realize co-catalytic ester exchange and esterification reactions in the multi-stage structure.

Benefits of technology

It significantly improves catalytic activity, enhances the stability and reuse performance of the catalyst, simplifies the biodiesel production process, and improves the yield and production efficiency of biodiesel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500103A_ABST
    Figure CN119500103A_ABST
Patent Text Reader

Abstract

The invention provides a transition metal oxide loaded aluminum oxide hierarchical pore catalytic material as well as a preparation method and application thereof. The hierarchical pore catalytic material Mo / V coated H-Al2O3 is prepared from hierarchical pore H-Al2O3 and an active component loaded on the hierarchical pore H-Al2O3, and the active component mainly comprises V2MoO8. The preparation method of Mo / V-coated H-Al2O3 mainly comprises the following steps: introducing ammonium molybdate and ammonium metavanadate into hierarchical pore H-Al2O3 through a continuous impregnation method, and preparing by combining with a calcination process. The solid acid catalyst with the hierarchical pore catalytic material Mo / V coated H-Al2O3 as the double active centers has a macroporous-mesoporous hierarchical pore structure and a high specific surface area, macropores are beneficial to transfer and diffusion of oil reactants and products, and carbon accumulation is reduced; the double-acid catalytic sites show synergistic catalysis, so that the catalytic activity of the material is remarkably improved, and the material can be used as a catalyst to convert oil into biofuel in one step. As a catalyst, the Mo / V-coated H-Al2O3 material has the advantages of wide raw material application range, high catalytic activity, good stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation and application of multiphase catalysts, and in particular to a transition metal oxide-loaded alumina multi-level porous catalytic material and a preparation method and application thereof. Background Art

[0002] At present, biodiesel is produced industrially by reacting oil (triglyceride) or fatty acid with low-carbon alcohol (such as methanol). In actual production, the cost of raw materials accounts for about 75-80% of the total cost of biodiesel production, which is a key factor restricting the development of biodiesel. In order to reduce production costs, waste oil (such as frying oil and waste oil) can be used as economically advantageous raw materials. However, these waste oils have high free fatty acids (FFAs) and water content, and are multi-component, high viscosity, large mass transfer resistance, unstable and complex systems, and higher requirements will be placed on the performance of their conversion catalysts. Alkaline catalysts are not suitable for such waste oils, and FFAs and water can react with alkali to undergo saponification, making the catalyst irreversibly deactivated. Solid acid catalysts have low sensitivity to FFAs and water, so in the process of preparing biodiesel, no pretreatment step is required to remove these FFAs and water. In addition, acid catalysts can simultaneously catalyze triglyceride transesterification and free fatty acid esterification to generate biodiesel, so highly acidic waste oils can be converted into biodiesel in one pot, simplifying the commonly used complex and cumbersome separation and purification processes.

[0003] In order to improve resource utilization efficiency, the development of efficient heterogeneous catalysts for waste oil conversion is of great significance for clean production and sustainable development. The ideal solid acid catalyst for biodiesel production should have a high density Double acid sites, multi-level pore structure and large specific surface area can achieve high catalytic activity, promote material transfer, and show significant catalytic stability. Therefore, for biodiesel catalysts, selecting a carrier with a high specific surface area and multi-level pore structure is one of the effective strategies to improve catalyst performance, which is beneficial to the circulation and diffusion of triglyceride macromolecular raw materials and can improve the accessibility of active sites, thereby increasing the yield of biodiesel.

[0004] Transition metal oxides are effective active ingredients in solid acid catalysts for biomass conversion. Dual acid sites show multifunctional catalytic activity. In the process of biodiesel production, single metal active components are easily leached. In order to prevent or reduce dissolution, multi-metal oxides are doped to form mixed metal oxides, which can improve catalytic stability through interaction. In the oil conversion reaction, macromolecular oil raw materials have the characteristics of high viscosity and large molecules, which have mass transfer resistance and obstacles on the surface of conventional heterogeneous catalysts, significantly affecting the catalyst activity. Therefore, in terms of heterogeneous catalyst carriers, multi-level pore structure carriers are superior to traditional microporous structure carriers. Their larger pore size structure and abundant through-hole channels can reduce the diffusion resistance of macromolecular reactants and enhance the mass transfer of macromolecular oil materials. The multi-level structure is also easy to functionalize with multi-metal oxides. Moreover, the multi-level pore carrier has a large specific surface area and a higher total porosity, which can provide more active sites and improve the exposure of catalytic active sites.

[0005] The activity and availability of the catalytic centers of heterogeneous catalysts and their surface mass transfer properties determine the performance of the catalyst. The pore size distribution and continuity of the catalyst carrier have an important influence on its specific surface area, availability of active centers and material mass transfer rate. At present, the main problems of heterogeneous acid catalysts used in biodiesel production are low catalytic activity, insufficient stability and easy carbon deposition, which leads to poor stability and catalytic ability of biodiesel production and low production efficiency. Summary of the invention

[0006] In view of this, it is necessary to research and develop a heterogeneous acid catalytic material with a large specific surface area and a multi-level pore structure, which can effectively improve the contact between the reaction oil reactant and the active site, promote the mass transfer rate of the reaction substrate on the catalyst surface, and assemble the composite metal oxide active center in this multi-level structure, giving the catalyst the multifunctionality of co-catalyzing transesterification and esterification, so as to solve the mass transfer resistance and obstacle problems of triglyceride macromolecules (fat macromolecules) in the multi-phase catalyst structure, increase the stability of the catalytic active center, improve its catalytic performance in the conversion of waste oil, and improve the production efficiency of biodiesel. Therefore, the present invention provides a transition metal oxide-supported alumina multi-level pore catalytic material and its preparation method and application.

[0007] Specifically, the technical solution adopted by the present invention is:

[0008] A transition metal oxide-supported alumina hierarchical catalytic material, represented by Mo / V@H-Al2O3, comprises hierarchical H-Al2O3 and active components supported on the H-Al2O3, wherein the hierarchical H-Al2O3 is Al2O3 with a three-dimensional ordered macroporous-mesoporous hierarchical pore structure, the active component is a mixed high-valent oxide of Mo and V, and the active component mainly comprises V2MoO8.

[0009] Furthermore, the active components also include V2O5 and AlVMoO7, that is, the active components include V2MoO8, V2O5 and AlVMoO7.

[0010] Furthermore, the active components also include Al2(MoO4)3, that is, the active components include V2MoO8, Al2(MoO4)3, V2O5 and AlVMoO7.

[0011] The multi-level porous H-Al2O3 as the carrier of the active component has a macropore diameter of 215-225nm, a mesopore diameter of 8.2-12.3nm, and a specific surface area of ​​220-232m 2 / g, pore volume is 0.40-0.45cm 3 / g.

[0012] The multi-level porous catalytic material Mo / V@H-Al2O3 has a macroporous-mesoporous multi-level porous structure with a surface area of ​​120-148m 2 / g, the macropore diameter is 210-230nm, the mesopore diameter is 5.7-9.6nm, and the pore volume is 0.21-0.32cm 3 / g.

[0013] The present invention also provides a method for preparing the multi-level porous catalytic material, comprising the steps of:

[0014] Preparation of Mo@H-Al2O3: First, multi-level porous H-Al2O3 and ammonium molybdate ((NH4)2MoO4) are used as raw materials, and calcined at 450-850°C to obtain H-Al2O3 multi-level porous material loaded with high-valent molybdenum oxide: Mo@H-Al2O3;

[0015] Preparation of Mo / V@H-Al2O3: using the multi-level porous material Mo@H-Al2O3 and ammonium metavanadate (NH4VO3) as raw materials, high-temperature calcination treatment is performed at 450-850°C to obtain the multi-level porous catalytic material: Mo / V@H-Al2O3;

[0016] The mass ratio of the total mass of (NH4)2MoO4 and NH4VO3 to the mass of the multi-level porous H-Al2O3 is 1:0.24-0.32.

[0017] Wherein, in the step of preparing Mo@H-Al2O3 and the step of Mo / V@H-Al2O3, each calcination time is preferably 4-8 hours to ensure complete calcination and decomposition of ammonium molybdate and ammonium metavanadate, and to reduce undesirable aggregation of the main catalytic components.

[0018] The steps of preparing Mo@H-Al2O3 include: using an impregnation method to immerse the multi-level porous H-Al2O3 in a (NH4)2MoO4 solution to obtain a H-Al2O3 multi-level porous material loaded with (NH4)2MoO4; calcining the H-Al2O3 multi-level porous material loaded with ammonium molybdate at 550-650°C for 4-8h to obtain the multi-level porous material Mo@H-Al2O3. The mass ratio of the multi-level porous H-Al2O3 to the (NH4)2MoO4 solid is 1:0.1-0.2. The mass ratio of (NH4)2MoO4 to water in the (NH4)2MoO4 solution is preferably 1:4-8.

[0019] The steps of preparing Mo / V@H-Al2O3 include: firstly using NH4VO3 solution and the multi-level porous material Mo@H-Al2O3 as raw materials, and using an impregnation method.

[0020] A Mo@H-Al2O3 multi-level porous material loaded with NH4VO3 is obtained; and then the Mo@H-Al2O3 multi-level porous material loaded with NH4VO3 is calcined to prepare the multi-level porous catalytic material: Mo / V@H-Al2O3.

[0021] The steps of preparing Mo / V@H-Al2O3 include: using a continuous impregnation method to impregnate the multi-level porous material Mo@H-Al2O3 into an NH4VO3 solution, drying, and obtaining the Mo@H-Al2O3 multi-level porous material loaded with NH4VO3; calcining the Mo@H-Al2O3 multi-level porous material loaded with NH4VO3 at 550-650°C for 4-8h to obtain the multi-level porous catalytic material Mo / V@H-Al2O3. The mass ratio of the multi-level porous H-Al2O3 carrier to the NH4VO3 solid is 1:0.1-0.3. The mass ratio of NH4VO3 to water in the NH4VO3 solution is preferably 1:4-8.

[0022] Wherein, in order to increase the catalyst activity, the mass ratio of ammonium molybdate to ammonium metavanadate is 1:0.65-1.20.

[0023] The multi-level porous H-Al2O3 is mainly prepared by evaporation-induced self-assembly method using monodisperse ordered polystyrene (PS) microspheres and Pluronic P123 triblock copolymer as templates. Specifically, the H-Al2O3 carrier is synthesized by double template method using PS microspheres as hard templates and Pluronic P123 triblock copolymer as soft templates. Among them, the full name of Pluronic P123 triblock copolymer is: polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, and its molecular formula is: PEO-PPO-PEO.

[0024] Furthermore, the synthesis method of the multi-level porous H-Al2O3 includes: first adding Pluronic P123 triblock copolymer, HNO3 solution (65wt.%) and Al(OiPr)3 (aluminum triisopropoxide) into ethanol and stirring to dissolve; then adding the PS microspheres and stirring thoroughly; then drying at 50-70°C and static conditions to obtain a H-Al2O3 carrier precursor; calcining the H-Al2O3 carrier precursor to prepare the multi-level porous H-Al2O3.

[0025] In the process of synthesizing the H-Al2O3 carrier, PS microspheres with a diameter of about 280-300 nm are used as macroporous templates, and Pluronic P123 triblock copolymers are used as mesoporous templates. In order to obtain a stable multi-level porous H-Al2O3 and a multi-level porous structure with an appropriate macropore-mesoporous ratio, the mass ratio of the Pluronic P123 triblock copolymer, HNO3 solution and Al(OiPr)3 is preferably 1:1.8-2.2:2.1-2.5, and more preferably 1:2.1:2.1. If the amount of solvent ethanol is too large, the drying time will increase; if it is too small, the precursor compound will not be completely dissolved, so its amount is preferably 5-8 times the mass of the Pluronic P123 triblock copolymer; more preferably 6 times.

[0026] If the amount of PS microspheres is too large, more macropores will be formed, causing instability of the carrier structure; if it is too small, more mesopores will be formed, which is not conducive to the mass transfer of oil macromolecules. Therefore, the amount of PS microspheres is preferably 0.9-1.1 times the mass of Pluronic P123 triblock copolymer, and more preferably 1.05 times.

[0027] If the calcination temperature of the H-Al2O3 carrier precursor is too low and the calcination time is too short, the precursor will not be completely decomposed; if the calcination temperature is too high and the calcination time is too long, it is easy to cause structural damage. Therefore, the calcination temperature of the H-Al2O3 carrier precursor is 650-750°C and the calcination time is 4-6h.

[0028] The PS microspheres are synthesized by emulsifier-free emulsion polymerization technology. The specific synthesis method includes: adding styrene and water to a reactor, heating to 60-80°C and stirring for 0.5-1.5 hours under a nitrogen environment, and then adding a K2S2O8 initiator to react for 20-30 hours to obtain a milky white mixed solution, and then cooling the milky white mixed solution to room temperature, inducing the monodisperse PS microspheres to assemble into a densely packed state through a high-speed centrifuge to obtain a white solid; drying the white solid and crushing it into powder to obtain PS microspheres, which can be used as a macroporous template.

[0029] If the volume ratio of styrene to water is too small or too large, it is difficult to form a uniform emulsion, which affects the polymerization reaction of styrene. Therefore, the volume ratio of styrene to water is preferably 1:12-18, more preferably 1:15.

[0030] If the amount of K2S2O8 initiator added is small, the polymerization reaction cannot be effectively initiated; if the amount added is large, the polymer quality is affected and the production cost is increased. Therefore, the amount of styrene to initiator added is preferably 1:0.01-0.015 mL / g, more preferably 1:0.012 mL / g.

[0031] The present invention also provides an application of the above-mentioned multi-level porous catalytic material Mo / V@H-Al2O3 in catalyzing oil to produce biofuel. Wherein, the oil can be pure oil or waste oil, and the pure oil includes vegetable oil, animal oil, etc. The vegetable oil can be soybean oil, peanut oil, melon seed oil, rapeseed oil, cottonseed oil, jatropha seed oil, etc. The water content in the waste oil is 0-5.8%, and the free fatty acid content is 0-62.7mg(KOH) / g; it can be waste frying oil, waste kitchen oil, waste rancid oil, etc. Preferably, the amount of the multi-level porous catalytic material Mo / V@H-Al2O3 is 6-10wt% of the mass of the oil.

[0032] Preferably, the hierarchical porous catalytic material Mo / V@H-Al2O3 is used in catalyzing the production of biodiesel using oil and methanol as raw materials.

[0033] The above technical solution provided by the present invention has the following advantages:

[0034] (1) The multi-level porous catalytic material Mo / V@H-Al2O3 has a macroporous-mesoporous multi-level pore structure and a high specific surface area. The macropores are conducive to the transfer and diffusion of oil reactants and products, and reduce carbon accumulation; and The double acid catalytic sites exhibit a synergistic catalytic effect, so that the catalytic activity of the multi-level porous catalytic material is significantly improved;

[0035] (2) The active components Mo and V in the multi-level porous catalytic material Mo / V@H-Al2O3 are evenly distributed on the multi-level porous H-Al2O3 carrier. It has Lewis acid catalytic center and strong acidity. It has good acid and water resistance, can synergistically catalyze triglyceride transesterification (oil transesterification) and free fatty acid esterification, and can also convert low-quality waste oil into biofuel in one pot. It is a promising and environmentally friendly solid acid catalyst.

[0036] (3) By using the multi-level porous catalytic material, waste oil and methanol are used as raw materials, triglycerides and free fatty acids in the waste oil can be converted into biofuels in one pot without the need for deacidification and dehydration of the waste oil in advance; in addition, under optimized operating conditions, the triglyceride conversion rate can reach 95.6%, and the free fatty acids can be completely converted into biofuels at the same time;

[0037] (4) The multi-level porous catalytic material Mo / V@H-Al2O3 has good reusability as a catalyst for catalyzing oil to generate biofuel.

[0038] Therefore, the entire production process of producing biofuels using the multi-level porous catalytic abrasion Mo / V@H-Al2O3 provided by the present invention as an oil catalyst and using oil and methanol as raw materials has the characteristics of high yield, short process, simplified process, green process, etc., and has industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 XRD patterns of different comparative hierarchical porous materials: AH-Al2O3-550℃, B.0.28V@H-Al2O3-550℃, C.0.28Mo@H-Al2O3-550℃, D.0.24Mo / V@H-Al2O3-550℃, E.0.28Mo / V@H-Al2O3-550℃, F.0.32Mo / V@H-Al2O3-550℃;

[0040] Figure 2 SEM images of PS microspheres (a), H-Al2O3 carrier (b) and 0.28Mo / V@H-Al2O3-550°C catalyst (c, d) provided in Example 1 of the present invention;

[0041] Figure 3 TEM images of the multi-level porous H-Al2O3 carrier (a, b) and 0.28Mo / V@H-Al2O3-550°C multi-level porous material (c, d) provided in Example 1 of the present invention; Mapping image of the multi-level porous catalyst;

[0042] Figure 4 N2 adsorption-desorption curves of the multi-level porous H-Al2O3 carrier and 0.28Mo / V@H-Al2O3-550℃ multi-level porous material provided in Example 1 of the present invention;

[0043] Figure 5 Py-IR spectra of the 0.28Mo / V@H-Al2O3-550°C hierarchical porous material provided in Example 1 of the present invention at different desorption temperatures;

[0044] Figure 6This is the EDS spectrum of the 0.28Mo / V@H-Al2O3-550℃ multi-level porous material provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is further described in detail below through specific implementation methods.

[0046] The terms used in the present invention are all commonly used terms in the relevant field. The raw materials, equipment, preparation processes, testing methods, etc. used, unless otherwise specified, are all existing technologies or common knowledge and conventional conditions in the relevant field.

[0047] The measurement method used in each embodiment is as follows:

[0048] Specific surface area measurement method: Micromeritics ASAP 2460 automatic specific surface and porosity analyzer was used to measure the specific surface area and pore size distribution of the sample by nitrogen adsorption-desorption at 120°C for 8 hours. After the measurement, the BET formula was used to calculate the specific surface area of ​​the sample based on the experimental data, and the pore volume and pore size distribution were calculated using the BJH method.

[0049] Triglyceride conversion rate (oil conversion rate) determination: Agilent 7890N gas chromatograph was used for determination, and the detector was FID detector. In this method, methyl heptadecanoate was used as the internal standard, n-hexane was used as the solvent, and fatty acid methyl ester was determined based on the retention time of the reference standard. The oil conversion rate was calculated according to the following formula:

[0050]

[0051] In the formula, X ME is the oil conversion rate, ∑A ME It can be defined as the total peak area of ​​oil. As represents the peak area of ​​the internal standard, Vs represents the volume of the internal standard, unit: mL; Cs represents the concentration of the internal standard, unit: mg / mL; m represents the mass of the sample, unit: mg.

[0052] Determination of free fatty acid conversion rate: The conversion rate of free fatty acid esterification was calculated based on the change ratio of the acid value of the substrate reaction mixture before and after the reaction. The acid ester determination was carried out according to GB5530-85.

[0053] Example 1

[0054] This embodiment provides a transition metal oxide-loaded alumina multi-level porous catalytic material and a preparation method thereof, wherein the preparation method mainly comprises the steps of PS microsphere synthesis, multi-level porous H-Al2O3 carrier preparation and multi-level porous catalyst Mo / V@H-Al2O3 preparation.

[0055] S1: Synthesis of PS microspheres: 16 mL of styrene (pre-washed 3 times with 2 mol / L NaOH and then washed with distilled water to pH ≈ 7) and 240 mL of water were added to the reactor and then heated to 70 ° C under N2 environment. After stirring for 0.5 h, 0.28 g of K2S2O8 initiator was added to the reaction mixture, and then the polymerization reaction was carried out in N2 atmosphere for 24 h. After the obtained milky white mixture was cooled to room temperature, the monodisperse PS microspheres were induced to assemble into a densely packed state by a high-speed centrifuge. Finally, the obtained white solid was dried at 60 ° C and crushed into powder for use as a macroporous template.

[0056] S2: 3.0 g of Pluronic P123 triblock copolymer, 4.5 mL of 65 wt.% HNO3 solution and 6.1 g of Al(OiPr)3 were added to 60 mL of ethanol and stirred vigorously for 5 h. Then, 3.1 g of PS microspheres were added to the above solution and stirred for another 5 min, and then placed in a 60°C water bath to dry under static conditions. Finally, the obtained solid was calcined at 700°C for 5 h to obtain a multi-level porous H-Al2O3 with a three-dimensional ordered macroporous-mesoporous structure, which was used as a carrier for the subsequent preparation of multi-level porous catalytic materials.

[0057] S3: Preparation of hierarchical porous catalytic material Mo / V@H-Al2O3 by continuous isochoric impregnation method: (NH4)2MoO4 and NH4VO3 are used as precursors of Mo and V high-valent oxides, respectively. First, an aqueous solution containing the required amount of ammonium molybdate and a hierarchical porous H-Al2O3 carrier are stirred at room temperature for 12 hours, the resulting product is dried at 80°C for 12 hours, and calcined at 550°C for 5 hours to obtain Mo@H-Al2O3, and then the calcined Mo@H-Al2O3 sample is continuously impregnated with the same volume of ammonium metavanadate solution, the obtained sample is dried at 80°C for 12 hours, and calcined at 550°C for 5 hours to obtain a hierarchical porous catalytic material. The hierarchical porous catalytic material sample is named x-Mo / V@H-Al2O3-y, wherein the mass ratio of the total amount of (NH4)2MoO4 and NH4VO3 to the hierarchical porous H-Al2O3 in the preparation process of the hierarchical porous catalytic material Mo / V@H-Al2O3, hereinafter referred to as "MoV raw material ratio", is represented by x; y represents the calcination temperature of the hierarchical porous catalytic material precursor; wherein the mass ratio of ammonium molybdate to water in the ammonium molybdate aqueous solution is 1:5, and the mass ratio of ammonium metavanadate to water in the ammonium metavanadate solution is 1:5. In this embodiment, the amount of ammonium molybdate aqueous solution is 450g, the amount of H-Al2O3 carrier is 500g, the amount of ammonium metavanadate solution is 390g, the mass ratio of the multi-level pore H-Al2O3 carrier to (NH4)2MoO4 is 1:0.15, the mass ratio of the multi-level pore H-Al2O3 carrier to NH4VO3 is 1:0.13, 549g of intermediate product Mo@H-Al2O3 is obtained, and 591g of the final product multi-level pore catalytic material Mo / V@H-Al2O3 is obtained. Therefore, the multi-level pore catalytic material Mo / V@H-Al2O3 obtained in this embodiment can be expressed as 0.28Mo / V@H-Al2O3-550℃.

[0058] Embodiment 2-9

[0059] Examples 2-9 respectively provide a multi-level porous catalytic material Mo / V@H-Al2O3, whose structure and preparation method are basically the same as those of Example 1, and the main differences are shown in Table 1 below.

[0060] Table 1 MoV raw material ratio and calcination temperature for preparation of hierarchical porous catalytic material Mo / V@H-Al2O3

[0061] Example MoV Raw Material Ratio Ammonium molybdate solution(g) Ammonium metavanadate solution (g) Calcination temperature (℃) Example 2 0.20 321 278 550℃ Example 3 0.24 386 334 550℃ Example 4 0.32 514 446 550℃ Example 5 0.28 450 390 450℃ Example 6 0.28 450 390 650℃ Example 7 0.28 450 390 750℃ Example 8 0.28 504 336 550℃ Example 9 0.28 336 504 550℃

[0062] Among them, the mass ratio of (NH4)2MoO4 and NH4VO3 in Example 2-7 is 15:13, the mass ratio of (NH4)2MoO4 and NH4VO3 in Example 8 is 3:2, and the mass ratio of (NH4)2MoO4 and NH4VO3 in Example 9 is 2:3.

[0063] Comparative Examples 1-6

[0064] Comparative Example 1 provides a Mo@H-Al2O3 multi-level porous material, which is basically the same as the preparation method of the Mo / V@H-Al2O3 multi-level porous material provided in Example 1, with the main difference being that: Step S3 of this comparative example is: 840g of ammonium molybdate aqueous solution (containing 140g of ammonium molybdate) and 500g of H-Al2O3 carrier are stirred at room temperature for 12h, the resulting product is dried at 80°C for 12h, and calcined at 550°C for 5h, finally obtaining 596g of Mo@H-Al2O3 multi-level porous material, which can be expressed as 0.28Mo@H-Al2O3-550°C.

[0065] Comparative Example 2 provides a V@H-Al2O3 multi-level porous material, which is basically the same as the preparation method of the Mo / V@H-Al2O3 multi-level porous material provided in Example 1, with the main difference being that: Step S3 of this comparative example is: 840g of ammonium metavanadate solution (containing 140g of ammonium metavanadate) and 500g of H-Al2O3 carrier are stirred at room temperature for 12h, the resulting product is dried at 80°C for 12h, and calcined at 550°C for 5h, finally obtaining 603g of V@H-Al2O3 multi-level porous material, which can be expressed as 0.28V@H-Al2O3-550°C.

[0066] Comparative Example 3 provides a mesoporous m-Al2O3 porous material carrier, which is mainly different from the H-Al2O3 prepared in Example 1 in that: steps S1 and S3 are omitted in this comparative example, and only Pluronic P123 triblock copolymer is used as a template in step S2. The specific steps are: 3.0g of Pluronic P123 triblock copolymer, 4.5mL of 65wt.% HNO3 solution and 6.1g of Al(OiPr)3 are added to 60mL of ethanol and stirred vigorously for 5h; then, dried in a water bath at 60°C under static conditions; finally, the dried product is calcined at 700°C for 5h to obtain a mesoporous m-Al2O3 mesoporous material.

[0067] Comparative Example 4 provides an ordinary Al2O3 carrier, and its preparation method is basically the same as the m-Al2O3 mesoporous material provided in Comparative Example 3, with the main difference being that no template is added in this comparative example, that is, 4.5mL of 65wt.% HNO3 solution and 6.1g of Al(OiPr)3 are added to 60mL of ethanol and vigorously stirred for 5h; then, it is dried in a water bath at 60°C under static conditions; finally, the dried product is calcined at 700°C for 5h to obtain an ordinary Al2O3 carrier.

[0068] Comparative Example 5 provides a 0.28Mo / V@m-Al2O3-550℃ multi-level porous material. The main difference between it and the 0.28Mo / V@H-Al2O3-550℃ multi-level porous material provided in Example 1 is that this comparative example uses the m-Al2O3 mesoporous material synthesized in Comparative Example 3 to replace the multi-level porous structure H-Al2O3 carrier in step S3 of Example 1, and other methods and parameters are the same.

[0069] Comparative Example 6 provides a 0.28Mo / V@Al2O3-550℃ multi-level porous material. The main difference between it and the 0.28Mo / V@H-Al2O3-550℃ multi-level porous material provided in Example 1 is that this comparative example uses the ordinary Al2O3 carrier synthesized in Comparative Example 4 to replace the multi-level porous structure H-Al2O3 carrier in step S3 of Example 1, and other methods and parameters are the same.

[0070] (1) XRD analysis

[0071] In order to confirm the active components of the Mo / V@H-Al2O3 multi-level porous catalytic material, XRD analysis was performed on the multi-level porous H-Al2O3 carrier prepared in Example 1, 0.28Mo / V@H-Al2O3-550°C provided in Example 1, 0.24Mo / V@H-Al2O3-550°C provided in Example 3, 0.32Mo / V@H-Al2O3-550°C provided in Example 4, 0.32Mo@H-Al2O3-550°C provided in Comparative Example 1, and 0.28V@H-Al2O3-550°C provided in Comparative Example 2. The results are as follows Figure 1 shown.

[0072] The multi-level pore H-Al2O3 characteristic peak ( Figure 1 A) appears at 37.6°, 45.8°, and 67.0°. These peaks are the (311), (400), and (440) crystal plane diffraction peaks of γ-Al2O3 (JCPDS10-425), and the γ-Al2O3 phase can be detected in all catalysts. When a single precursor (NH4)2MoO4 or NH4VO3 is introduced into the multi-level porous H-Al2O3, the multi-level porous material obtained by calcination has a V of 0.28V@H-Al2O3-550℃( Figure 1 B), the typical XRD characteristic peaks of V2O5 appeared at 2θ=15.4°, 20.1°, 26.6°, 31.1°, 32.4°, 34.3°, and 51.2° (JCPDS 9-387, 45-1074); the multi-level porous material 0.28Mo@H-Al2O3-550℃( Figure 1 C), XRD spectrum shows XRD diffraction peaks attributed to Al2(MoO4)3 (JCPDS23-0764).

[0073] (NH4)2MoO4 and NH4VO3 are simultaneously introduced into the multi-level porous H-Al2O3, and the multi-level porous catalytic material 0.24Mo / V@H-Al2O3-550℃( Figure 1 D) The peaks at 21.6°, 23.4°, 28.2°, 33.1° and 34.0° (JCPDS18-0851) are caused by the V2MoO8 crystal phase. Continuing to increase the total loading of (NH4)2MoO4 and NH4VO3 in the multi-level porous H-Al2O3, the generated multi-level porous catalytic material 0.28Mo / V@H-Al2O3-550℃( Figure 1 E) The characteristic peaks of V2O5 and AlVMoO7 (JCPDS 46-0687) crystals appeared. When the total loading of (NH4)2MoO4 and NH4VO3 reached 0.32, the multi-level porous catalytic material 0.32Mo / V@H-Al2O3-550℃( Figure 1 F) It can be observed that the characteristic diffraction peaks of Al2(MoO4)3, V2O5, AlVMoO7, and V2MoO8 crystals are significantly enhanced, and the diffraction peak of MoO3 appears (JCPDS 47-1081).

[0074] The above XRD results show that the transition metal precursors (NH4)2MoO4 and NH4VO3 are loaded on the multi-level porous H-Al2O3, and after high-temperature calcination, (NH4)2MoO4 and NH4VO3 are completely converted into their corresponding metal oxides or mixed solid oxides. In particular, there is a strong interaction in this mixed solid high-valent oxide, which is not easy to dissolve in the reaction system, increasing the catalytic stability of the transition metal oxide.

[0075] (2) Scanning electron microscopy (SEM) analysis

[0076] PS microspheres, multi-level porous H-Al2O3 carrier and multi-level porous catalytic material 0.28Mo / V@H-Al2O3-550℃ were analyzed by SEM. Figure 2 As shown. PS microspheres are uniform, with a diameter of about 285nm, and are orderly arranged and tightly packed ( Figure 2 a). During the carrier synthesis process, the Al2O3 precursor Al(OiPr)3 is immersed in the macroporous template PS microspheres, and the Al(OiPr)3 molecules penetrate into the ordered sphere voids, then hydrolyze and precipitate to form an intermediate composite structure, and then the template is removed by calcination, leaving an ordered porous Al2O3 framework. Multi-level porous H-Al2O3 carrier ( Figure 2b) presents an ordered porous morphology, in which the macropore diameter is about 220nm, slightly smaller than the diameter of the PS microspheres, which may be caused by the shrinkage of the PS microspheres under high temperature heat treatment. After the introduction of Mo and V, 0.28Mo / V@H-Al2O3-550℃ multi-level porous material ( Figure 2 c, d) The ordered multi-level pore structure of the multi-level pore H-Al2O3 carrier is maintained. This three-dimensional ordered multi-level pore structure can effectively promote the mass transfer of reactant molecules, shorten the mass transfer path, and improve the catalytic performance.

[0077] (3) Transmission electron microscopy (TEM) characterization

[0078] In order to further confirm the structure of the hierarchical porous catalytic material Mo / V@H-Al2O3, TEM was used for characterization. The results are as follows Figure 3 shown. Figure 3 (a, b) are transmission electron micrographs of the multi-level porous H-Al2O3. It can be clearly seen that there are abundant macropores and mesopores on the surface and in the crystal of the multi-level porous H-Al2O3 carrier, and the pore structure is evenly arranged with almost the same pore size. The PS microspheres produce macropores after thermal decomposition. Since the PS microspheres are closely connected, orderly mesopores are formed at the cross-linking points between the macropores. In addition, the mesopores left by the thermal decomposition of the Pluronic P123 triblock copolymer are evenly distributed on the pore walls of the macropores. Figure 3 (c, d) are TEM images of the multi-level porous catalytic material 0.28Mo / V@H-Al2O3-550℃. It can be seen that after the introduction of the high-valent oxides of Mo and V in the active center, the multi-level porous structure of the multi-level porous H-Al2O3 is well preserved and not destroyed, so that the multi-level porous catalytic material Mo / V@H-Al2O3 also has a three-dimensional multi-level porous structure. In addition, in order to explore the dispersion of Mo and V high-valent oxides in the multi-level porous catalytic material Mo / V@H-Al2O3, a Mapping scan was performed, and it can be found that Mo and V high-valent oxides are introduced into the multi-level porous H-Al2O3 and are highly dispersed, providing rich catalytic active sites for the multi-level porous catalytic material Mo / V@H-Al2O3. Therefore, the TEM results further illustrate that the multi-level porous catalytic material of the present invention has a good multi-level porous structure and rich catalytic active sites, and has good catalytic activity and stability.

[0079] (4) N2 adsorption-desorption measurement

[0080] The H-Al2O3 carrier and the multi-level porous catalytic material Mo / V@H-Al2O3 provided in Examples 1, 2, and 3 were subjected to nitrogen adsorption-desorption measurements. The results are as follows: Figure 4As shown. The multi-level porous samples all show typical type IV isotherms, indicating the existence of a mesoporous structure. In addition, with the increase of relative pressure, capillary condensation occurs, and an H2-type hysteresis loop is formed between P / P0=0.40-0.88. Another adsorption phenomenon occurred at P / P0>0.88, indicating the existence of large pores. Moreover, an approximately linear intermediate cross-section appeared in the low-pressure part, which is related to the unrestricted single-layer or multi-layer adsorption on the multi-level porous material, further confirming the formation of a large pore structure. The above nitrogen adsorption-desorption results verify that the multi-level porous catalytic material Mo / V@H-Al2O3 has a macroporous-mesoporous multi-level porous structure. Among them, the specific surface area of ​​the multi-level porous catalytic material Mo / V@H-Al2O3 is 120-148m 2 / g, pore volume is 0.21-0.32cm 3 / g, the average pore size is 7.26-9.51nm; the specific surface area of ​​the multi-level porous catalytic material 0.28Mo / V@H-Al2O3-550℃ is the largest, which is 148.1m 2 / g, pore volume 0.29cm 3 / g, and the average pore size is 9.51nm.

[0081] (5) Py-IR spectroscopy analysis

[0082] The acidity of the multi-level porous catalytic material 0.28Mo / V@H-Al2O3-550℃ was measured using Py-IR technology. The Py-IR measured at different desorption temperatures was as follows: Figure 5 As shown in the Py-IR spectrum of the multi-level porous material, at 1447 cm -1 and 1611cm -1 The two characteristic IR peaks at 1540 cm -1 and 1636cm -1 The two characteristic peaks at 1487 cm-1 indicate the presence of Bronsted acid sites in 0.28Mo / V@H-Al2O3-550℃. -1 The characteristic Py-IR peaks appearing at can be attributed to the superposition of Lewis and Bronsted acid sites. In addition, the characteristic peaks of Lewis and Bronsted acid sites can still be detected at a desorption temperature of 350°C, indicating that the acid sites of the multi-level porous catalytic material Mo / V@H-Al2O3 are relatively strong. The above Py-IR results show that the multi-level porous catalytic material Mo / V@H-Al2O3 contains Lewis-Bronsted double acid sites, has the performance of catalyzing triglyceride transesterification and free fatty acid esterification reactions, and can convert waste oil into biofuels in one pot.

[0083] (6) EDS spectral analysis

[0084] The element composition and content of the hierarchical porous catalytic material 0.28Mo / V@H-Al2O3-550℃ were analyzed by EDS spectroscopy. Figure 6 The mass percentages of Mo, V, Al and O in the catalyst are 12.15wt.%, 12.48wt.%, 31.65wt.% and 43.72wt.%, respectively, and the contents of Mo and V are basically consistent with the theoretical values.

[0085] Example 9 Application of multi-level pore catalytic materials in oil-to-biofuel conversion

[0086] This embodiment provides the application of the multi-level porous catalytic materials prepared by Examples 1-8, Comparative Examples 1-2 and Comparative Examples 5-6 and the multi-level porous H-Al2O3 used in Example 1 in oil-to-biofuel conversion. The specific method includes: using soybean oil and methanol as raw materials to prepare biodiesel using an intermittent high-pressure reactor, adding 1000g soybean oil and 1280g methanol to a reactor, and then adding 8wt% of the above-mentioned multi-level porous catalytic materials by weight of soybean oil, stirring the reaction at 130°C for 8h, and the stirring speed is 500rpm. After the reaction is completed, it is cooled to room temperature, the catalyst is filtered, and the excess methanol is evaporated under reduced pressure, and the evaporated methanol is used. Then, glycerol is separated by centrifugation, and the oil conversion rate of the product is detected by gas chromatography. The biofuel conversion rate is as shown in Table 2.

[0087] Table 2 Conversion rate of soybean oil catalyzed by different porous materials

[0088]

[0089] Combined with Table 1, from the results of catalytic soybean oil conversion using multi-level porous H-Al2O3, Example 1, Comparative Examples 1-2 and Comparative Examples 5-6 as catalysts, the multi-level porous catalytic material 0.28Mo / V@H-Al2O3-550℃ provided in Example 1 has a high catalytic activity, and the high-valent oxides of the active components Mo and V have a synergistic effect. In addition, the multi-level macroporous-mesoporous structure has a significant effect on improving the catalytic performance of the catalytic material in the process of converting oil to biofuel.

[0090] From the grease conversion rates of Examples 1-4, the grease conversion rate in the multi-level porous catalytic material first increases with the increase of the MoV raw material ratio, reaches the highest when the ratio is 0.28, and then decreases.

[0091] From the oil conversion rates of Examples 1 and 5-7, the oil conversion rate in the multi-level porous catalytic material first increases and then decreases as the calcination temperature of the precursor increases during its formation, and at a calcination temperature of 550°C, the oil conversion rate reaches a maximum of 95.6%.

[0092] Example 10 Application of the multi-level porous catalytic material Mo / V@H-Al2O3 in the conversion of waste oil into biofuel

[0093] In this embodiment, waste cooking oil and methanol are used as raw materials, and biodiesel is prepared by an intermittent high-pressure reactor. 1000g of waste cooking oil and 1280g of methanol are added to the reactor, and then 0.28Mo / V@H-Al2O3-550℃ multi-stage catalytic material provided in Example 1 with a mass of 8wt% of soybean oil is added as a catalyst, and the reaction is stirred at 130℃ for 8h, and the stirring speed is 500rpm. After the reaction is completed, it is cooled to room temperature, the catalyst is filtered, and the excess methanol is evaporated under reduced pressure, and the evaporated methanol is used. Then, glycerol is separated by centrifugation, and the product is tested for the conversion rate of fatty acid methyl ester by gas chromatography. Among them, the main impurity composition of the waste cooking oil and the biofuel conversion rate are shown in Table 3.

[0094] Table 3 Application of hierarchical porous materials in the conversion of waste cooking oil into biofuels

[0095]

[0096]

[0097] Example 11: Recycling of Mo / V@H-Al2O3 multi-level catalytic materials in oil-to-biofuel conversion

[0098] The 0.28Mo / V@H-Al2O3-550℃ multi-level porous material used in Example 1 was recovered as a catalyst, washed three times with cyclohexane and methanol respectively, and then dried and the method provided in Example 1 was repeated. Referring to Example 9, soybean oil and waste cooking oil were used as raw materials to prepare biodiesel in an intermittent high-pressure reactor. The catalytic effect of repeated use is shown in Table 4. Among them, the water content in the waste cooking oil in this example is: 1.8%, and the acid value is: 20.6mg(KOH) / g.

[0099] Table 4. Grease conversion rate of recycled multi-level porous Mo / V@H-Al2O3 catalytic materials (%)

[0100] raw material Use once Use 2 times Use 3 times Use 4 times Use 5 times Soybean Oil 95.6 93.8 91.2 86.8 82.3 Waste cooking oil 92.5 89.6 85.7 80.8 75.7

[0101] As can be seen from Table 4, as the number of reuses increases, the catalytic activity decreases. After the catalyst is reused 4 times, the oil conversion rate of the multi-level porous catalytic material Mo / V@H-Al2O3 catalyzing oil to produce biofuel is still over 80%, indicating that the multi-level porous catalytic material Mo / V@H-Al2O3 provided by the present invention has good reuse performance as a catalyst.

[0102] The multi-level porous catalytic material Mo / V@H-Al2O3 provided in the embodiment of the present invention uses PS microspheres and block copolymer P123 as templates, and adopts evaporation-induced self-assembly method to prepare a multi-level porous H-Al2O3 carrier with macroporous-mesoporous structure, and then introduces different amounts of Mo and V precursors ammonium molybdate and ammonium metavanadate into the multi-level porous H-Al2O3 carrier by continuous impregnation method, and combines with calcination process to prepare a multi-level porous solid acid catalyst Mo / V@H-Al2O3 with dual active centers, wherein the main active component in the multi-level porous solid acid catalyst is V2MoO8, and also includes V2O5 and AlVMoO7, or further includes Al2(MoO4)3. The multi-level porous catalytic material Mo / V@H-Al2O3 has good catalytic performance in the process of converting oil to biofuel, especially it can convert waste oil into biofuel in one step.

[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.

Claims

1. A transition metal oxide-supported alumina multi-level porous catalytic material, characterized in that: Expressed as Mo / V@H-Al2O3, it includes multi-level porous H-Al2O3 and active components loaded on the multi-level porous H-Al2O3, wherein the multi-level porous H-Al2O3 is Al2O3 with a three-dimensional ordered macroporous-mesoporous multi-level porous structure, and the active components mainly include V2MoO8.

2. The multi-level porous catalytic material according to claim 1, characterized in that: The active components also include V2O5 and AlVMoO7.

3. The multi-level porous catalytic material according to claim 2, characterized in that: The active component also includes Al2(MoO4)3.

4. A method for preparing the multi-level porous catalytic material according to any one of claims 1 to 3, comprising the steps of: Preparation of Mo@H-Al2O3: First, multi-level porous H-Al2O3 and ammonium molybdate are used as raw materials, and calcined at 450-850°C to obtain H-Al2O3 multi-level porous material loaded with high-valent molybdenum oxide: Mo@H-Al2O3; Preparation of Mo / V@H-Al2O3: using the multi-level porous material Mo@H-Al2O3 and ammonium metavanadate as raw materials, calcining at 450-850° C. to obtain the multi-level porous catalytic material: Mo / V@H-Al2O3; in, The mass ratio of the total mass of ammonium molybdate and ammonium metavanadate to the multi-level porous H-Al2O3 is 1:0.24-0.

32. The multi-level porous H-Al2O3 has a macropore diameter of 215-225 nm, a mesopore diameter of 8.2-12.3 nm, a specific surface area of ​​220-232 m² / g, and a pore volume of 0.40-0.45 cm 3 / g.

5. The preparation method according to claim 4, characterized in that The steps of preparing Mo@H-Al2O3 include: impregnating the multi-level porous H-Al2O3 into an ammonium molybdate solution by an impregnation method, drying, and obtaining an H-Al2O3 multi-level porous material loaded with ammonium molybdate; calcining the H-Al2O3 multi-level porous material loaded with ammonium molybdate at 550-650°C for 4-8 h to obtain the multi-level porous material Mo@H-Al2O3; wherein the mass ratio of the porous material H-Al2O3 to ammonium molybdate is 1:0.1-0.

2.

6. The preparation method according to claim 5, characterized in that The steps of preparing Mo / V@H-Al2O3 include: using a continuous impregnation method to impregnate the multi-level porous material Mo@H-Al2O3 into an ammonium metavanadate solution, drying, and obtaining the Mo@H-Al2O3 multi-level porous material loaded with ammonium metavanadate; calcining the Mo@H-Al2O3 multi-level porous material loaded with ammonium metavanadate at 550-650°C for 4-8 hours to obtain the multi-level porous catalytic material; wherein the mass ratio of the porous material H-Al2O3 to the ammonium metavanadate is 1:0.1-0.

3.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The mass ratio of ammonium molybdate to ammonium metavanadate is 1:0.65-1.

20.

8. The preparation method according to claims 4-6, characterized in that: The multi-level porous H-Al2O3 is mainly synthesized by using PS microspheres as hard templates and Pluronic P123 triblock copolymers as soft templates through evaporation-induced self-assembly, wherein the diameter of the PS microspheres is 280-300 nm.

9. The preparation method according to claim 8, characterized in that The synthesis method of the H-Al2O3 carrier comprises: firstly adding a Pluronic P123 triblock copolymer, an HNO3 solution (65wt.%) and Al(OiPr)3 into ethanol and stirring to dissolve; then adding the PS microspheres and stirring sufficiently; then drying at 50-70°C and under static conditions to obtain a H-Al2O3 carrier precursor; calcining the H-Al2O3 carrier precursor at 650-750°C for 4-6 h; wherein the mass ratio of the Pluronic P123 triblock copolymer, the HNO3 solution and the Al(OiPr)3 is 1: 1.8-2.2: 2.1-2.5, and the amount of the PS microspheres used is 0.9-1.1 times the mass of the Pluronic P123 triblock copolymer.

10. The preparation method according to claim 9, characterized in that The PS microsphere synthesis method comprises: adding styrene and water to a reactor in a volume ratio of 1:12-18, heating to 60-80°C and stirring for 0.5-1.5 h under a nitrogen environment, and then adding a K2S2O8 initiator to react for 20-30 h to obtain a milky white mixed solution, and then cooling the milky white mixed solution to room temperature, inducing monodisperse PS microspheres to assemble into a tightly packed state through a high-speed centrifuge to obtain a white solid; drying the white solid and crushing it into powder to obtain PS microspheres; wherein the amount of styrene and K2S2O8 initiator added is 1:0.01-0.015 mL / g.

11. Use of the multi-level porous catalytic material according to any one of claims 1 to 3 in catalyzing oil to produce biofuel, wherein: The amount of the multi-level porous catalytic material used is 6-10 wt % of the mass of the oil.

12. The use according to claim 11, characterized in that The oil is waste oil, and the water content of the waste oil is 0-5.8%, and the free fatty acid content is 0-62.7 mg (KOH) / g.